Pengaruh Ciri Kepribadian terhadap Intimacy pada Dewasa Muda yang Menjalin Hubungan Romantis - Setiawati, Linda; Nurwianti, Fivi; Kilis, Grace (Universitas Negeri Surabaya, 2018)
The aim of this research is to examine the impact of vigilant, devoted, and self-sacrificing personality styles on intimacy (engagement, communication, shared friends) among young adults in romantic relationships (dating/married). A total of 1000 respondents aged 20-40 years old completed questionnaires on personality styles (Personality Self-Portrait) and intimacy (Personal Assessment of Intimacy in Relationships). Data analysis using Structural Equation Modeling (SEM) shows a significant impact of self-sacrificing personality styles on engagement (γ = -0,511, p < 0,01) and communication (γ = -0,361, p < 0,01). There are also significant influences of vigilant (γ = -0,225, p < 0,05) and devoted personality styles (γ = 0,132, p < 0,05) to shared friends. The impact of self-sacrificing personality styles indicates the importance of both parties’ involvement in influencing their relationship. Besides, being too sensitive (vigilant personality styles’ characteristic) and having a sense of comfort in relationships with others (devoted personality styles’ characteristic) could influence how individuals engage in social relationships outside their romantic relationships. Key words: Intimacy, personality styles, romantic relationshipsAbstrak: Penelitian ini bertujuan melihat pengaruh ciri kepribadian vigilant, devoted, dan self-sacrificing, terhadap intimacy (engagement, communication, shared friends) pada dewasa muda yang sedang menjalin hubungan romantis (berpacaran/menikah). Sebanyak 1000 responden berusia 20-40 tahun mengisi alat ukur ciri kepribadian (Personality Self-Portrait) dan intimacy (Personal Assessment of Intimacy in Relationships). Hasil analisis menggunakan Structural Equation Modeling (SEM) menunjukkan pengaruh ciri kepribadian self-sacrificing yang signifikan terhadap engagement (γ = -0,511, p < 0,01) dan communication (γ = -0,361, p < 0,01). Selain itu ditemukan pula pengaruh ciri kepribadian vigilant (γ = -0,225, p < 0,05) dan devoted (γ = 0,132, p < 0,05) yang signifikan terhadap shared friends, juga pengaruh status hubungan yang signifikan terhadap communication (γ = 0,102, p < 0,01). Pengaruh ciri kepribadian self-sacrificing yang signifikan menekankan pentingnya keterlibatan kedua pihak dalam mempengaruhi kualitas hubungan mereka. Selain itu, kepekaan yang terlalu tinggi (karakteristik ciri kepribadian vigilant) dan rasa nyaman akan hubungan dengan orang lain (karakteristik ciri kepribadian devoted) dapat mempengaruhi individu dalam menjalin hubungan dengan lingkungan sosial di luar hubungannya.